Hermeneutika dalam Tafsir al-Qur’an: antara Pembacaan Kontekstual dan Risiko Desakralisasi Makna - Farhan, Ahmad Ali (Maliki Interdisciplinary Journal, 2025)
This article examines the application of hermeneutics in Qur’anic interpretation by highlighting the tension between contextual readings and the risk of desanctifying the sacred meaning of revelation. Hermeneutics, as a contemporary interpretive approach, offers new possibilities for understanding the Qur’an in response to modern social and intellectual challenges. However, this approach also raises significant epistemological and theological concerns, particularly when the Qur’an is treated primarily as a historical-linguistic text subject to the interpreter’s subjectivity. This study demonstrates that an unrestrained application of hermeneutics may undermine the sanctity of Qur’anic meaning and weaken its divine authority. The findings emphasize the necessity of an integrative framework that balances contextual interpretation with the methodological principles of ulūm al-Qur’an, ensuring both the relevance and the sacredness of the Qur’anic text are preserved.